Intraoperative visualisation of functional structures facilitates safe frameless stereotactic biopsy in the motor eloquent regions of the brain. (4th July 2018) - Zhang, Jia-Shu; Qu, Ling; Wang, Qun; Jin, Wei; Hou, Yuan-Zheng; Sun, Guo-Chen; Li, Fang-Ye; Yu, Xin-Guang; Xu, Ban-Nan; Chen, Xiao-Lei
Abstract: Background: For stereotactic brain biopsy involving motor eloquent regions, the surgical objective is to enhance diagnostic yield and preserve neurological function. To achieve this aim, we implemented functional neuro-navigation and intraoperative magnetic resonance imaging (iMRI) into the biopsy procedure. The impact of this integrated technique on the surgical outcome and postoperative neurological function was investigated and evaluated. Method: Thirty nine patients with lesions involving motor eloquent structures underwent frameless stereotactic biopsy assisted by functional neuro-navigation and iMRI. Intraoperative visualisation was realised by integrating anatomical and functional information into a navigation framework to improve biopsy trajectories and preserve eloquent structures. iMRI was conducted to guarantee the biopsy accuracy and detect intraoperative complications. The perioperative change of motor function and biopsy error before and after iMRI were recorded, and the role of functional information in trajectory selection and the relationship between the distance from sampling site to nearby eloquent structures and the neurological deterioration were further analyzed. Results: Functional neuro-navigation helped modify the original trajectories and sampling sites in 35.90% (16/39) of cases to avoid the damage of eloquent structures. Even though all the lesions were high-risk of causing neurological deficits, no significant difference was found between preoperative and postoperative muscle strength. After data analysis, 3mm was supposed to be the safe distance for avoiding transient neurological deterioration. During surgery, the use of iMRI significantly reduced the biopsy errors ( p = 0.042) and potentially increased the diagnostic yield from 84.62% (33/39) to 94.87% (37/39). Moreover, iMRI detected intraoperative haemorrhage in 5.13% (2/39) of patients, all of them benefited from the intraoperative strategies based on iMRI findings. Conclusions: Intraoperative visualisation of functional structures could be a feasible, safe and effective technique. Combined with intraoperative high-field MRI, it contributed to enhance the biopsy accuracy and lower neurological complications in stereotactic brain biopsy involving motor eloquent areas.